Effects of spinosad and spinetoram on larval mortality, adult emergence, progeny production and mating in Cadra cautella (Walk.) (Lepidoptera: Pyralidae). (September 2020) - Sammani, A.M.P.; Dissanayaka, D.M.S.K.; Wijayaratne, L.K.W.; Morrison, W.R.
Abstract: The bacterial formulations, spinosad and spinetoram, were evaluated for their efficacy in suppressing development and mating success in Cadra cautella (Walk.) (Lepidoptera: Pyralidae), the almond moth. A dilution series of spinosad and spinetoram was sprayed on rice flour. Rice flour samples sprayed with water served as the control. Late instar C. cautella larvae were introduced onto spinosad-, spinetoram-, or water-treated rice flour. The first experiment tested the effects of spinosad and spinetoram on larval mortality, as well as emergence of adults and progeny at different insecticide concentrations. In the second experiment, the mating success of C. cautella adults that had emerged from larvae exposed to spinosad was tested inside a cubicle. Both spinosad and spinetoram increased larval mortality, whereas both compounds reduced adult emergence and progeny production. Natural mating was reduced in the presence of the synthetic sex pheromone ( Z, E )-9, 12-tetradecadienyl acetate. However, exposure of C. cautella larvae to spinosad did not alter mating in adult progeny. Spinosad was more effective than spinetoram at suppressing C. cautella development. The study concludes that both spinosad and spinetoram suppress the development of immatures of C. cautella to the adult stage as well as mating. Thus, the both compounds can be used to protect stored grains from infestation by C. cautella. Highlights: Spinosad and spinetoram were evaluated against Cadra cautella larvae. Both insecticides suppressed larval survival, adult emergence and progeny production. Spinosad did not alter mating of adult Cadra cautella following exposure as larvae. Spinosad is more effective than spinetoram.